Specialization of production — A factor of integration - Albrecht Iwersen (Intereconomics, 1977)
The statute of the Council of Mutual Economic Assistance (CMEA) assigns to the institutions of the council the task to promote the process of specialization and cooperation in the production sector of the national economies. The development of the relations between the member countries indicates that especially in recent years this production specialization became a more and more important factor of integration.
Keywords: 330; CMEA